Physics Education Students' Understanding of X-Ray Concepts and Applications: An Interview Study on Stambuk Students 2021 - Sembiring, Grace Kania Violentina; Fadilah, Nurul; Sitio, Apri Ananta (Manunggal Halim Jaya, 2025)
This research aims to explore the understanding of Physics Education students of the class of 2021 regarding the concept and application of X-rays in various fields. Through a qualitative approach with an in-depth interview method, this study involved three participants to gain insight into their understanding of the basic principles of X-rays, the formation process, as well as aspects of radiation safety and risk. The results show that although students have a basic understanding of X-rays as electromagnetic radiation, there are misconceptions about the scope of their application and the principles of physics that underlie the formation of X-rays. The study also found limitations in lecture materials in emphasizing aspects of radiation protection and its applications outside the medical world, which is important to strengthen a comprehensive understanding. Based on these findings, the study provides recommendations to develop a more applicable curriculum, improve practicum facilities, and integrate cross-disciplinary studies so that students have a broader understanding of X-rays.